2016
DOI: 10.21315/aamjaf2016.11.s1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effective Corporate Governance and Financial Reporting in Japan

Abstract: This paper examines corporate governance in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…The conclusion that good corporate governance practice has a positive relationship on audit quality, it is supported the previous research by (Beisland et al, 2015;Collier & Gregory, 1996;Gul & Leung, 2004;Makni et al, 2012). And also this empirical research found in line by a previous empirical study by Carcello et al, 2010;Riguen et al, 2018 stated that good corporate governance structure demands better audit quality and more trusted financial report (Rahman & Bremer, 2016) and it is reflecting of audit quality of financial report.…”
Section: Analysis and Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The conclusion that good corporate governance practice has a positive relationship on audit quality, it is supported the previous research by (Beisland et al, 2015;Collier & Gregory, 1996;Gul & Leung, 2004;Makni et al, 2012). And also this empirical research found in line by a previous empirical study by Carcello et al, 2010;Riguen et al, 2018 stated that good corporate governance structure demands better audit quality and more trusted financial report (Rahman & Bremer, 2016) and it is reflecting of audit quality of financial report.…”
Section: Analysis and Resultssupporting
confidence: 81%
“…The results of our study provide empirical research that corporate governance positively correlation on audit quality, which can be explained that good corporate governance structure positive and demand better audit quality (Beisland et al, 2015;Carcello et al, 2010;Collier & Gregory, 1996;Gul & Leung, 2004;Makni et al, 2012;Riguen et al, 2018) and more trusted financial report (Rahman & Bremer, 2016).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations